Digital Payments and Monetary Policy Transmission in Indonesia: An Islamic Economic Perspective - Pantas, Pribawa E; Othman, Norfaizah; Yunus, Mawar Murni; Puad, Noor Aimi Mohamad (IJISH (International Journal of Islamic Studies and Humanities), 2026)
This study investigates whether the rapid expansion of digital payment systems reshapes the transmission of monetary policy in Indonesia, incorporating an Islamic economic perspective. Using monthly data from 2018M01 to 2024M12, this study employs the Autoregressive Distributed Lag (ARDL) model, along with impulse response function (IRF) and dynamic multiplier analyses, to capture both equilibrium and dynamic effects. The results reveal that cashless transactions significantly reduce inflation, indicating improved transaction efficiency and lower price rigidities. Moreover, the interaction between digital payments and policy interest rates strengthens the transmission mechanism, suggesting that financial digitalisation acts as a transmission accelerator. Islamic financial development is also found to contribute to inflation stability, reflecting the role of risk-sharing and asset-backed financing in reducing speculative pressures. The dynamic analyses confirm that the disinflationary effect of digital payments is persistent and stabilises in the long run. This study contributes to the literature by integrating digital finance and Islamic finance into a unified macroeconomic framework, offering new insights into the evolving structure of monetary transmission in emerging economies.